Manajemen Mutu Pendidikan Dalam Meningkatkan Proses Pembelajaran Siswa Kelas X Farmasi Di SMK Muhammadiyah Minggir Tahun 2023 - yulianta, eka (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
Education is an important component in determining the success of the educational process and one of the factors in improving the quality of education in Indonesia. Quality education is the hope and dream of society. The current rapid level of development demands increasingly higher availability of human resources. Thus, adequate quality and output is something that must be produced by vocational high schools as educational units whose basic aim is to prepare quality people both intellectually and for their role in community life. This research uses a qualitative approach with descriptive analysis. The research subjects were school principals, head of curriculum, teachers and heads of study programs in the pharmacy department. The data collection techniques used are the interview method, observation method, and documentation method, from which primary and secondary data will be obtained which will then be analyzed together to draw conclusions. Based on the results of research that the author has conducted, it can be concluded that the quality of education at Muhammadiyah Minggir Vocational School in supporting the learning process is quite good. However, the management of the quality of education in these schools has not been realized properly, as efforts have not been optimal to support the effectiveness of the learning process and the lack of funding for teachers to improve their competence. The obstacles experienced are the lack of human resources in the administration and infrastructure fields as well as the funds coming in for the procurement process and infrastructure management process which are still slow.